Pengaruh Kepemimpinan Kepala Madrasah, Motivasi Kerja, dan Kedisiplinan Terhadap Kinerja Guru Pada Madrasah Aliyah Negeri 2 Tapin di Rantau - Jayen, Fredy; Kadir, Abdul; Amrulloh, Rifqi; Yani, Akhmad (Universitas Hang Tuah, 2022)
The purpose of this study was to determine the influence of the Madrasah Principal's Leadership, Work Motivation, and Discipline on Teacher Performance at Madrasah Aliyah Negeri 2 Tapin in Rantau. The research method used is an analytical survey. This type of research is explanatory research. The population in this study were all teachers at the Madrasah Aliyah Negeri 2 Tapin in Rantau in 2020 as many as 40 people consisting of 15 PNS teachers and 25 honorary teachers. The sample in this research is using total sampling technique. Data collection techniques using questionnaires, documentation, interviews, and observation. Validity and reliability tests were carried out on research instruments. Data were analyzed with multiple linear regression analysis with the classical assumption test. The results showed that the Madrasah Principal's Leadership, Work Motivation, and teacher discipline simultaneously had a significant effect on the performance of Madrasah Aliyah Negeri 2 Tapin teachers in Rantau. Madrasah Principal Leadership, Work Motivation, and teacher discipline have a partially significant effect on the performance of Madrasah Aliyah Negeri 2 Tapin teachers in Rantau. The leadership of the Madrasah Principal has a dominant significant influence on the performance of the Madrasah Aliyah Negeri 2 Tapin teachers in Rantau.